Determinants of Customer loyalty: service quality and satisfaction: Penentu Loyalitas Nasabah : Kualitas Pelayanan dan Kepuasan - Nora, Liza; Kaamilah, Nur Afiifah; Harun, Siti Hafnidar (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to explain the role of satisfaction in influencing service quality to customer loyalty at PT. BPRS Harta Insan Karimah. The method used in this study is a quantitative method that is associative. The source of this research is using primary data. The sample collection technique used is purposive sampling technique, with the number of samples tested by 96 respondents from customers. The data collection technique is using a questionnaire distributed via Google Form to the customers who are domiciled in Tangerang. The data analysis method in this study uses the Structural Equation Model (SEM), using the WarpPLS 7.0 approach. The results of this study indicate that service quality has a significant effect on customer loyalty and service quality with customer satisfaction as a mediation has a significant effect on customer loyalty. This means that the customer satisfaction variable is a partial mediation, which can affect directly or indirectly between the service quality variable and customer loyalty.